Pemungutan Cukai Plastik Sebagai Upaya Pengurangan Sampah Plastik - Notika Rahmi; Selvi Selvi (Jurnal Pajak Vokasi (JUPASI), 2021)
This study aims to analyze the collection of plastic excise as an effort to reduce plastic waste in Indonesia. This research is a qualitative research by observing, interviewing and analyzing the documents. The results of the study indicate that the proposed plastic excise tariff of 200 Rupiahs per bag is still considered too low so that researchers consider it will not have a significant impact on reducing plastic consumption in Indonesia. In addition, commitment from the government, employers and the wider community is needed to support this plastic excise tax policy.